Assessing the individual relationships between physical test improvements and external load match parameters in male professional football players—a brief report - Byrkjedal, Per Thomas; Bjørnsen, Thomas; Luteberget, Live Steinnes; Ivarsson, Andreas; Spencer, Matt (Frontiers in Sports and Active Living, 2024)
Purpose: To explore if a meaningful improvement in physical performance following an in-season strength training intervention can be related to external load match parameters at an individual level in professional male football players.Methods: Eight male professional football players (25.4±3.1 yrs, 184.1±3.4 cm, 79.3±2.2 kg) completed a 10-week strength intervention period, in addition to football specific training and matches. Commonly used physical and external load measures were assessed pre-and postintervention. Physical performance improvements had to exceed the measurements typical error and the smallest worthwhile difference (SWD) to be considered meaningful. SWD and non-overlap of all pairs (NAP) analysis was performed to assess external load match parameters pre-and postintervention period. A Bayesian pairwise correlation analysis was performed to assess relationships between changes in physical performance and external load match parameters.Results: Three players displayed meaningful improvements in 2 to 5 measures of physical performance. However, positive changes greater than SWD, and positive effects in NAP results were shown for all players in external load match parameters. Kendall's Tau correlation analysis showed evidence (base factor >3) for only one correlation (maximum speeddecelerations, τ = -.62), between the changes in physical performance and external load measures, while the remaining comparisons were unrelated.The findings suggest that improvements in physical performance may not necessarily translate to improvements in external load match parameters. Further research, with larger sample sizes, is needed to understand potential mechanisms between acute and chronic physical performance changes and football external load parameters during training and matches.